Pemberian Psikoedukasi Kepada Masyarakat Melalui Media Poster - Anggraeni, Anggi; Silvianis Diwanti, Yusrinda; Hamidah, Nurlaela (UIR Press, 2022)
To optimize children’s development, the parent needs to understand a basic understanding of about developmental milestones that can help during their children’s growth. The parent needs to improve their knowledge broaden and deeper into itregarding the children development. Focusing on parents’ knowledge as the initial intervention is the most important thing. This situation is because parent knowledge regarding the children’s development will imply on their application practical and behavior in their parenting styles. This community service program is integrated with the Developmental Psychology 1st course, which involved 240 students. For one semester, students have been prepared themselves regarding all provided developmental psychology theories;, developmental stages, which start from prenatal, infant to early childhood which covering physical development, cognitive, language development, social, emotional, and moral, also human development in Islam based on AlQur’an and Hadith. As the final assignment, the student should create a psychoeducation poster for society. Furthermore, the student will explain the poster. The posters that- themed “development” as an education form (psychoeducation intervention), which are expected to improve the targeted group’s knowledge (including parents, teachers, medical team, and the general society) regarding children development. The provided knowledge regarding children developmental stages from prenatal to 11-12 years old in were motoric, cognitive, language, and social emotion. The community service was held on August 10th-20th, 2021, in 56 West Java and West Kalimantan cities.